APPROACH OF MUSLIM THEOLOGIANS TO PROPHECY - Muhammad Anisur Rahman; Saeed Ahmed; Fozya Ayob (Journal of Religion and Society, 2025)
After acknowledging the existence of Allah (SWT), the second most important belief in Islam is the belief in Prophethood. The belief in Prophethood and Messengership is that Allah (SWT) sent a series of Prophets to guide humanity. Each Prophet was sent to a specific nation or region, commanding them to follow the oneness of Allah (Tawhid) and His commandments. The last of the Prophets in this series was Prophet Muhammad (PBUH). Due to the significance of the concept of Prophethood, Islamic theologians (Mutakallimun) have given special attention to the idea of Prophethood and have presented important doctrines regarding it. Additionally, they have extensively discussed the various sources and miracles that confirm the authenticity of the Prophets. Below are the key opinions of ancient and contemporary theologians regarding Prophethood. Keywords: Prophet, Messenger, Theologians, Miracle, Al-Ghazali, Ibn Taymiyyah, Shah Waliullah, Shabbir Ahmad Usmani